2013
DOI: 10.1177/1468796813483730
|View full text |Cite
|
Sign up to set email alerts
|

‘No smoke without fire’: Strategies of coping with stigmatised migrant identities

Abstract: This paper examines how ethnicity informs the ways in which Romanian migrants in the UK cope with stigmatisation. Instead of assuming ethnicity’s relevance, our purpose is to examine how responses to stigmatisation may or may not become ethnicised. We consider two strategies. The first strategy invokes and reinforces the salience of ethnicity, albeit in a negative and thus still stigmatised way. Instead of countering stigma with a positive reappraisal of ‘Romanianness’, some Romanians seek to transfer the stig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 34 publications
2
66
3
Order By: Relevance
“…Some of the participants of this study did indeed report everyday encounters with British people who expected them to 'look different'. As other studies have also shown (Morosanu and Fox, 2013), participants used strategies against such stigma. One of them was claiming a European identity, because it promotes a broader solidarity that includes Romanians.…”
Section: Analysis: Representations Of Europe and Cosmopolitanismmentioning
confidence: 79%
See 2 more Smart Citations
“…Some of the participants of this study did indeed report everyday encounters with British people who expected them to 'look different'. As other studies have also shown (Morosanu and Fox, 2013), participants used strategies against such stigma. One of them was claiming a European identity, because it promotes a broader solidarity that includes Romanians.…”
Section: Analysis: Representations Of Europe and Cosmopolitanismmentioning
confidence: 79%
“…This is because whiteness comes in shades and it is mediated by other markers of difference (McDowell, 2009). In the case of Romanians, they are often associated with the Roma gypsy (Morosanu and Fox, 2013), who are deeply racialized (Tileaga, 2006). This may explain why Romanians are often seen as outside the norm of European whiteness (see Fox, Morosanu and Szilassy, 2012).…”
Section: Analysis: Representations Of Europe and Cosmopolitanismmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the literature on discrimination has focused on non-European immigrants in Europe, there is starting to be a large body of literature focusing on discrimination of Eastern Europeans in Western Europe (Scheibner and Morrison 2009) more generally, and Romanians in Europe (see Fox et al 2012, Moroşanu and Fox 2013, McMahon 2016, more particularly. This latter point is one also made in Gijsberts and McGinnity (2012)'s paper, but from the perspective of the destination country responses to new migrants.…”
Section: Romanian Emigration To London and Parismentioning
confidence: 99%
“…Back (1996) provides ample evidence of the fragility of cross-ethnic friendships, and the more or less subtle ways in which they are tinged by racism. Individuals may combine enthusiasm towards some forms of difference with negative feelings towards others, illustrating the ambivalence of cosmopolitanism (Skrbiš and Woodward 2007;Moroşanu and Fox 2013 …”
Section: The Indifference To Differencementioning
confidence: 99%